(untitled) (Medical Forum Monthly, 2024)
Objective: To identify the common causes of Acute Renal Failure (ARF) in Nishtar Hospital Multan Study Design: Prospective observational study Place and Duration of study: This study was conducted at Medical Wards, Nishtar Hospital Multan from September 2012 to March 2013. Materials and Methods: One hundred and thirty six (136) patients presented with Acute Renal Failure to Nishtar Hospital of ages 15 and above. Results: Fifty three patients (39%) were males and 83(61%)were females. Mean age of patients was 40.43±18.56 years. Our study showed that common causes of ARF were diarrhea with or without vomiting (22%), septicemia (22%), obstetric causes like septic abortion and APH/PPH (19.11%),obstructive uropathy (11%), hair dye ingestion (9.6%), glomerulonephritis (7.35%), nephrotoxins (5.9%), hemolysis (4.4%) and cardiac failure (3.7%). Conclusion: Diarrhea with/without vomiting,sepsis, post-partum and ante-partum hemorrhage, septic abortion, obstructive uropathy, hair dye, glomerulonephritis, nephrotoxic drugs, hemolysis and cardiac failureare the common causes of acute renalfailure in our setup.ARFis associated with high morbidity and mortality. So all these causes should be managed aggressively to avoid this life threatening complication.